Structure-Based Drug Design for Targeting IRE1: An in Silico Approach for Treatment of Cancer - Poustforoosh, Alireza; Faramarz, Sanaz; Nematollahi, Mohammad Hadi; Mahmoodi, Mehdi; Azadpour, Mahdiyeh (Drug Research, 2023)
Background Endoplasmic Reticulum (ER) stress and Unfolded Protein Response (UPR) play a key role in cancer progression. The aggregation of incorrectly folded proteins in the ER generates ER stress, which in turn activates the UPR as an adaptive mechanism to fix ER proteostasis. Inositol-requiring enzyme 1 (IRE1) is the most evolutionary conserved ER stress sensor, which plays a pro-tumoral role in various cancers. Targeting its’ active sites is one of the most practical approaches for the treatment of cancers.Objective In this study, we aimed to use the structure of 4μ8C as a template to produce newly designed compounds as IRE1 inhibitors.Methods Various functional groups were added to the 4μ8C, and their binding affinity to the target sites was assessed by conducting a covalent molecular docking study. The potential of the designed compound for further in vitro and in vivo studies was evaluated using ADMET analysis.Results Based on the obtained results, the addition of hydroxyl groups to 4μ8C enhanced the binding affinity of the designed compound to the target efficiently. Compound 17, which was constructed by the addition of one hydroxyl group to the structure of 4μ8C, can construct a strong covalent bond with Lys907. The outcomes of ADMET analysis indicated that compound 17 could be considered a drug-like molecule.Conclusion Our results revealed that designed compound 17 could inhibit IRE1 activity. Therefore, this designed compound is a remarkable inhibitor of IRE1 and introduces a promising therapeutic strategy for cancer treatment.
Keywords: cancer; UPR response; IRE1; 4μ8C; molecular docking; In-silico methods